2018
DOI: 10.9758/cpn.2018.16.1.18
|View full text |Cite
|
Sign up to set email alerts
|

From Neurons to Social Beings: Short Review of the Mirror Neuron System Research and Its Socio-Psychological and Psychiatric Implications

Abstract: The mirror neuron system (MNS) is a brain network activated when we move our body parts and when we observe the actions of other agent. Since the mirror neuron’s discovery in research on monkeys, several studies have examined its network and properties in both animals and humans. This review discusses MNS studies of animals and human MNS studies related to high-order social cognitions such as emotion and empathy, as well as relations between MNS dysfunction and mental disorders. Finally, these evidences are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 151 publications
0
38
0
5
Order By: Relevance
“…According to the Singapore Mental Health Study [6], the prevalence of SI among those with lifetime MDD was 43.6%, wherein approximately 31.5% and 28.2% of individuals planned and attempted suicide respectively. MDD has been known as a social and neuronal mental illness representing a complex mechanism of mental activity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Singapore Mental Health Study [6], the prevalence of SI among those with lifetime MDD was 43.6%, wherein approximately 31.5% and 28.2% of individuals planned and attempted suicide respectively. MDD has been known as a social and neuronal mental illness representing a complex mechanism of mental activity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The human brain contains a distinct class of neurons called the mirror neuron system (MNS), which discharge both when individuals perform an action, and when they observe another person performing an action with a similar intention ( Lago-Rodriguez et al, 2013 ). It is generally accepted that the MNS plays functional roles in intention understanding ( Bonini et al, 2010 ; Cacioppo et al, 2017 ), emotion recognition and empathy ( Molnar-Szakacs et al, 2009 ; Goodarzi et al, 2015 ), action imitation ( Molenberghs et al, 2009 ; Reynolds et al, 2015 ), self-recognition ( Jeon and Lee, 2018 ) and the evolution of language ( Zarr et al, 2013 ). The MNS transforms sensory information describing the actions of others into a motor representation, which is similar to the representation internally generated by an observer when they actually perform or imagine the action.…”
Section: Introductionmentioning
confidence: 99%
“…Modern neuroscience, notably through the discovery of mirror neurons (for a review see Jeon and Lee, 2018 ), confirmed many of these early intuitions on empathy (Decety et al, 2012 ).…”
Section: Relationships Are Embodiedmentioning
confidence: 91%